EFFECT OF DIETARY SUPPLEMENTATION OF ZINC ON GROWTH PERFORMANCE AND NUTRIENT UTILIZATION IN KIDS - Thakur, L; Nayak, S; Baghel, RPS; Patil, AK; Malpure, CD; Kumar, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Present study was undertaken to evaluate the effect of zinc supplementation on growth performance and nutrient utilization in kids. Twenty four goat kids (4-6 month age) were randomly divided into 4 groups (T1, T2, T3 and T4) having 6 kids each. Kids in the group T1 were fed basal diet which contained 29.02 mg Zn/kg DM from ingredients of ration without any additional Zn supplementation. Kids in the T2, T3 and T4 groups were fed the same basal diet with additive 20, 50 and 100 ppm Zn (as ZnSO4) in their diets, respectively. The study was conducted for 90 days. Digestion trial of 7 days was conducted towards the end of experiment to assess the digestibility of the nutrients. Results indicated significantly higher average body weight gain, crude protein (CP) digestibility and better feed efficiency in kids fed diet supplemented with 50.0 mg Zn/kg DM. From the results it was concluded that the Zn supplementation @ 50.0 mg/kg DM in basal diet significantly improved body weight (BW) gain, CP digestibility and feed efficiency ratio (FER) of kids.